SENSITIVITY AND SPECIFICITY OF DETECTING POLYPOIDAL CHOROIDAL VASCULOPATHY WITH EN FACE OPTICAL COHERENCE TOMOGRAPHY AND OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY. Issue 7 (July 2019) - de Carlo, Talisa E.; Kokame, Gregg T.; Kaneko, Kyle N.; Lian, Rebecca; Lai, James C.; Wee, Raymond
Abstract : Purpose: Determine sensitivity and specificity of polypoidal choroidal vasculopathy (PCV) diagnosis with structural en face optical coherence tomography (OCT) and OCT angiography (OCTA). Methods: Retrospective review of the medical records of eyes diagnosed with PCV by indocyanine green angiography with review of diagnostic testing with structural en face OCT and OCTA by a trained reader. Structural en face OCT, cross-sectional OCT angiograms alone, and OCTA in its entirety were reviewed blinded to the findings of indocyanine green angiography and each other to determine if they could demonstrate the PCV complex. Sensitivity and specificity of PCV diagnosis was determined for each imaging technique using indocyanine green angiography as the ground truth. Results: Sensitivity and specificity of structural en face OCT were 30.0% and 85.7%, of OCT angiograms alone were 26.8% and 96.8%, and of the entire OCTA were 43.9% and 87.1%, respectively. Sensitivity and specificity were improved for OCT angiograms and OCTA when looking at images taken within 1 month of PCV diagnosis. Conclusion: Sensitivity of detecting PCV was low using structural en face OCT and OCTA but specificity was high. Indocyanine green angiography remains the gold standard for PCV detection. Abstract : A study determining the sensitivity and specificity of polypoidal choroidal vasculopathy diagnosis using en face optical coherence tomography and optical coherence tomography angiography. Sensitivity of detecting polypoidal choroidal vasculopathy was low using en face optical coherence tomography and optical coherence tomography angiography, but specificity was high. Indocyanine green angiography remains the gold standard for polypoidal choroidal vasculopathy detection.